Metabolomic Profiling Reveals Social Hierarchy-Specific Metabolite Differences in Male Macrobrachium rosenbergii - Liping Li; Dayan Hu; Jiongying Yu; Xingyu Zheng; Miaoying Cai; Quanxin Gao; Shaokui Yi (Animals)
The giant freshwater prawn (Macrobrachium rosenbergii, GFP) is a highly valuable crustacean species in global aquaculture. However, a social hierarchy exists among the distinct male morphotypes, specifically blue-clawed males (BC), orange-clawed males (OC), and small males (SMs). In this study, to identify the specific metabolites among BC, OC, and SM, hemolymph samples were collected for the untargeted liquid chromatography–mass spectrometry metabolomics (LC–MS). A total of 172, 546, and 578 significantly different metabolites (SDMs) were identified in OC vs. BC, SM vs. BC, and SM vs. OC, respectively. Notably, creatine and glutamate in BC males likely enhance their aggressive behavior through improved energy metabolism. In the SM group, the up-regulation of prostaglandin E3, testosterone, and arachidonic acid may lead to premature gonadal maturation and enhance immunity. Serotonin, Glu-Pro, and pentanoylcarnitine detected in OC males reflect their physiological need for rapid growth and adaptation to social behaviors. In the SM group, the up-regulation of prostaglandin E3, arachidonic acid, and testosterone may promote premature gonadal maturation and enhance immunodominance. These findings will enhance the understanding of the physiological basis of social hierarchy formation in male GFPs from a metabolomics perspective.